Angular stable locking in a novel intramedullary nail improves construct stability in a distal tibia fracture model. Issue 3 (March 2022) - Zderic, Ivan; Gueorguiev, Boyko; Blauth, Michael; Weber, André; Koch, Roger; Dauwe, Jan; Schader, Jana Felicitas; Stoffel, Karl; Finkemeier, Christopher; Hessmann, Martin
Highlights: A biomechanical study investigating the competence of a novel angular stable nail for treatment of unstable distal tibia fractures. Angular stable locked nailing demonstrated higher relative construct stability under static and dynamic loading compared to conventional locked nailing. Enhanced relative construct stability is achieved without additional intraoperative procedures. Abstract: Introduction: Intramedullary nails are frequently used for treatment of unstable distal tibia fractures. However, insufficient fixation of the distal fragment could result in delayed healing, malunion or nonunion. Recently, a novel concept for angular stable nailing was developed that maintains the principle of relative stability and introduces improvements expected to reduce nail toggling, screw migration and secondary loss of reduction. The aim of this study was to investigate the biomechanical competence of the novel angular stable intramedullary nail concept for treatment of unstable distal tibia fractures, compared to a conventional nail locking in a human cadaveric model under dynamic loading. Materials and methods: Ten pairs of fresh-frozen human cadaveric tibiae with a simulated AO/OTA 42-A3.1 fracture were assigned to 2 groups for reamed intramedullary nailing using either a conventional (non-angular stable) Expert Tibia Nail (ETN) with 3 distal screws or the novel Tibia Nail Advanced (TNA) system with 2 distal angular stable locking low-profile retaining screws. The specimens were biomechanically tested under conditions including initial quasi-static loading, followed by progressively increasing combined cyclic axial and torsional loading in internal rotation until failure of the bone-implant construct. Both tests were monitored by means of motion tracking. Results: Initial nail toggling of the distal tibia fragment in varus and flexion under axial loading was lower for TNA compared to ETN, being significant in flexion, P  = 0.91 and P  = 0.03. After 5000 cycles, interfragmentary movements in terms of varus, flexion, internal rotation, axial displacement, and shear displacement at the fracture site were all lower for TNA compared to ETN, with flexion and shear displacement being significant, P  = 0.14, P  = 0.04, P  = 0.25, P  = 0.11 and P  = 0.04, respectively. Cycles to failure until both interfragmentary 5° varus and 5° flexion were significantly higher for TNA compared to ETN, P  = 0.04. Conclusion: From a biomechanical perspective, the novel angular stable intramedullary nail concept provides increased construct stability and maintains it over time while reducing the number of required locking screws without impeding the flexibility of the nail itself and resists better towards loss of reduction under dynamic loading, compared to conventional locking in intramedullary nailed unstable distal tibia fractures.